Culture studies in the field of international business research: A tale of two paradigms - Werner Vorm; Xin Li; Michael Jakobsen; Piehong Xie (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2015)
Purpose - The purpose of this paper is to describe the status of culture studies within the field of international business research, and to examine how two main paradigms - essentialism and social constructivism - relate to the discourse in this field. We analyze the main points of the two paradigms, and discuss how the relationship between them has evolved. Findings - We show that essentialism and social constructivism have a paradoxical relationship. They seem to be mutually exclusive, yet each offers unique insights into the notion of culture. Both are necessary for a complete understanding of culture, yet they cannot be integrated in any normal sense. We see the relationship between the two paradigms as paradoxical: that is, we see them as ontologically complementary yet epistemologically incommensurable. Taking inspiration from Bohr's principle of complementarity, we understand the two competing paradigms of culture studies as both necessary and yet as incompatible. Research limitations - Future research should help to improve the conceptual clarity with which the relationship between the two paradigms is portrayed here, thereby enhancing the empirical rigor of the argument we make in this paper. Practical implications - We encourage practitioners to learn how to switch, both sequentially and spatially, between the two paradigms of culture (fundamentally incommensurable though they are). This involves taking a "both/or" approach to the two paradigms. Originality/Value - We show for the first time that Bohr's complementarity principle is illustrative and useful for understanding the paradoxical relationship between essentialism and social constructivism. Inspired by two principles enunciated by Bohr - that of complementarity and that of classical concepts - we argue that the two competing paradigms are necessary yet 3 incommensurable. We therefore suggest that culture scholars switch between the two paradigms, instead of seeing each as negating the other.
hdl:10398/9257
Keywords: 330; Culture; Essentialist; Social constructivist; Complementary; Incommensurable; Internationale Betriebswirtschaftslehre; Kultursoziologie; Konstruktivismus